A ceramic thermal protection structure repairing agent, a preparation method thereof and a repairing method
Patent Information
- Application Number
- CN202611017835.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-08-28
AI Technical Summary
主要是针对纤维直径较长的碳化硅陶瓷基复合材料修复,无法实现短切陶瓷纤维随机网络材料和表面高辐射率涂层的修复
[0026] This invention discloses a method for preparing a ceramic thermal protection structure repair agent, comprising two components: resin and curing agent. Primarily, a colorless and transparent aluminum dihydrogen phosphate resin is obtained by adding phosphoric acid, aluminum hydroxide, and ethanol and stirring until homogeneous. Then, a non-sintering repair and curing material is prepared by uniformly mixing magnesium oxide, phosphate, polymer precursor ceramic, rare earth zirconate, high-entropy ceramic powder, zirconium oxide, and ethanol. This allows for curing at room temperature without high-temperature sintering. Surface heating can further accelerate the curing rate and improve repair efficiency. The repaired ceramic thermal protection structure exhibits excellent high-temperature resistance, while significantly reducing the difficulty and cost of repairing ceramic thermal protection structures.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic thermal protection structure repair agent preparation technology, specifically relating to a ceramic thermal protection structure repair agent and its preparation and repair methods. Background Technology
[0002] In the aerospace field, ceramic thermal protection structures mainly consist of coated ceramic tiles, strain gauges, adhesives, and composite material structures. Due to their superior high-temperature resistance, thermal insulation, and mechanical properties, they are core elements ensuring the safe and stable operation of critical equipment in extreme thermal environments. However, during aircraft flight, the surface ceramic thermal protection structure can suffer damage. Therefore, repairing damaged ceramic thermal protection structures is crucial to improving their reliability and durability. Patent application No. 202311326878.X discloses a repair agent and method for ceramic-based thermal protection materials used in aircraft. It primarily targets the repair of silicon carbide ceramic-based composite materials with long fiber diameters, but cannot repair short-cut ceramic fiber random network materials or high-emissivity surface coatings. Summary of the Invention
[0003] The problem this invention aims to solve is to achieve on-site repair of structures composed of ceramic fiber heat insulation tiles and surface coatings that can withstand temperatures up to 1500℃. The invention proposes a ceramic thermal protection structure repair agent, its preparation method, and the repair method thereof.
[0004] To achieve the above objectives, the present invention provides the following technical solution:
[0005] A method for preparing a ceramic thermal protection structural repair agent includes the following steps:
[0006] S1. Weigh out 40-60 parts of phosphoric acid, 14-30 parts of phosphate, 10-20 parts of aluminum hydroxide, 7-15 parts of magnesium oxide, 1-3 parts of zirconium oxide, 2-5 parts of polymer precursor ceramic, 0.5-2 parts of rare earth zirconate, 1-3 parts of high entropy ceramic powder, 10-100 parts of organic solvent and 10-100 parts of deionized water according to the following weight proportions:
[0007] S2. Dilute the phosphoric acid obtained in step S1 with deionized water to a mass fraction of 55%, then slowly pour it into aluminum hydroxide at a molar ratio of 1:2, and then place it in a constant temperature water bath at 70~90℃ for 3~4 hours to obtain the first mixture for later use.
[0008] S3. Place the first mixture obtained in step S1 in a rotary evaporator at 80~110℃, evaporate for 30~40 minutes, and remove it after naturally cooling to room temperature to obtain the second mixture;
[0009] S4. Add 40 parts of organic solvent to the second mixture obtained in step S2, stir evenly to obtain aluminum dihydrogen phosphate resin, and set aside for use;
[0010] S5. Place the magnesium oxide, phosphate, polymer precursor ceramic, rare earth zirconate, and high entropy ceramic powder weighed in step S1 into a mixer and stir for 30-50 minutes to obtain the third mixture, which is ready for use.
[0011] S6. Place the third mixture obtained in step S5 and the zirconium oxide weighed in step S1 into a high-speed shear reactor, then add 60 parts of organic solvent, mix at 3000~4000 rpm for 30~50 min; then use a ball mill to dry grind at 150~350 rpm for 3~4 h to obtain a non-sintering repair curing agent. After separating the aluminum dihydrogen phosphate resin obtained in step S4 and the non-sintering repair curing agent, obtain a ceramic thermal protection structure repair agent.
[0012] Furthermore, the polymer precursor in step S1 is composed of polyborosilazane.
[0013] Furthermore, the rare earth zirconate in step S1 is composed of La2Zr2O7.
[0014] Furthermore, the composition of the high-entropy ceramic powder in step S1 is Yb. 0.2 Ho 0.2 Er 0.2 Lu 0.2 , Tb 0.2 )2Si2O7, with a particle size of 400~800 nm.
[0015] Furthermore, the organic solvent in step S1 is ethanol.
[0016] Furthermore, the concentration of phosphoric acid in step S1 is 85 wt%.
[0017] One of the ceramic thermal protection structure repair agents includes aluminum dihydrogen phosphate resin and a non-sintering repair curing agent.
[0018] A method for repairing a ceramic thermal protection structure using the aforementioned repair agent includes the following steps:
[0019] Step 1. Use 200-800 grit sandpaper to sand the cracked areas on the coating surface, and then blow the repaired surface clean with clean air to obtain the pre-treated damaged area of the coating.
[0020] Step 2. Mix aluminum dihydrogen phosphate resin and non-sintering repair curing agent at a mass ratio of 3~4:1 to obtain the repair material;
[0021] Step 3. Apply repair material multiple times to the damaged area of the pretreated coating, so that the repaired surface is 1-2 mm higher than the initial surface;
[0022] Step 4. Use an infrared spotlight to heat the surface at 100–120°C for 10–15 hours at a distance of 5–10 cm from the surface to be repaired, in order to remove the solvent and solidify the material.
[0023] Step 5. After the repaired surface has cooled to room temperature, apply 5-10 wt% ammonia solution to the repaired surface 7-8 times, and seal it with plastic wrap for 40-50 minutes.
[0024] Step 6. Remove the plastic wrap, adjust the infrared spotlight to 120–150 ℃, heat it at a distance of 5–10 cm from the surface to be repaired for 6–8 hours to remove residual ammonia, and then let it stand for 24–48 hours to complete the surface repair.
[0025] The beneficial effects of this invention are:
[0026] This invention discloses a method for preparing a ceramic thermal protection structure repair agent, comprising two components: resin and curing agent. Primarily, a colorless and transparent aluminum dihydrogen phosphate resin is obtained by adding phosphoric acid, aluminum hydroxide, and ethanol and stirring until homogeneous. Then, a non-sintering repair and curing material is prepared by uniformly mixing magnesium oxide, phosphate, polymer precursor ceramic, rare earth zirconate, high-entropy ceramic powder, zirconium oxide, and ethanol. This allows for curing at room temperature without high-temperature sintering. Surface heating can further accelerate the curing rate and improve repair efficiency. The repaired ceramic thermal protection structure exhibits excellent high-temperature resistance, while significantly reducing the difficulty and cost of repairing ceramic thermal protection structures. Detailed Implementation
[0027] To further understand the invention's content, features, and effects, the following specific embodiments are provided and described in detail below:
[0028] Example 1:
[0029] A method for preparing a ceramic thermal protection structural repair agent includes the following steps:
[0030] S1. Weigh out 50 parts of phosphoric acid, 30 parts of phosphate, 10 parts of aluminum hydroxide, 8 parts of magnesium oxide, 2 parts of zirconium oxide, 3 parts of polymer precursor ceramic, 1 part of rare earth zirconate, 2 parts of high entropy ceramic powder, 100 parts of organic solvent and 100 parts of deionized water according to the weight ratio, and set aside for use.
[0031] Furthermore, the polymer precursor in step S1 is composed of polyborosilazane.
[0032] Furthermore, the rare earth zirconate in step S1 is composed of La2Zr2O7.
[0033] Furthermore, the composition of the high-entropy ceramic powder in step S1 is Yb. 0.2 Ho 0.2 Er 0.2 Lu 0.2 , Tb 0.2 )2Si2O7, with a particle size of 400~800 nm.
[0034] Furthermore, the organic solvent in step S1 is ethanol.
[0035] Furthermore, the concentration of phosphoric acid in step S1 is 85 wt%.
[0036] S2. The phosphoric acid obtained in step S1 is diluted with deionized water to a mass fraction of 55%, and then slowly poured into aluminum hydroxide at a molar ratio of 1:2. The mixture is then placed in a constant temperature water bath at 80°C and reacted for 3 hours to obtain the first mixture for later use.
[0037] S3. Place the first mixture obtained in step S1 in a rotary evaporator at 90°C, evaporate for 40 minutes, and remove it after naturally cooling to room temperature to obtain the second mixture;
[0038] S4. Add 40 parts of organic solvent to the second mixture obtained in step S2, stir evenly to obtain aluminum dihydrogen phosphate resin, and set aside for use;
[0039] S5. Place the magnesium oxide, phosphate, polymer precursor ceramic, rare earth zirconate, and high entropy ceramic powder weighed in step S1 into a mixer and stir for 45 minutes to obtain the third mixture, which is ready for use.
[0040] S6. Place the third mixture obtained in step S5 and the zirconium oxide weighed in step S1 into a high-speed shear reactor, then add 60 parts of organic solvent and mix at 3000~4000 rpm for 50 min; then dry grind at 300 rpm for 4 h using a ball mill to obtain a non-sintering repair curing agent. After separating the aluminum dihydrogen phosphate resin obtained in step S4 and the non-sintering repair curing agent, obtain a ceramic thermal protection structure repair agent.
[0041] Furthermore, in this embodiment, the mass ratio of aluminum dihydrogen phosphate resin to the non-sintering repair curing agent used in the repair is 3.5:1.
[0042] Example 2:
[0043] The difference between this embodiment and Embodiment 1 is that in this embodiment, step S1 involves weighing 50 parts of phosphoric acid, 20 parts of phosphate, 10 parts of aluminum hydroxide, 8 parts of magnesium oxide, 2 parts of zirconium oxide, 3 parts of polymer precursor ceramic, 1 part of rare earth zirconate, 2 parts of high entropy ceramic powder, 100 parts of organic solvent, and 100 parts of deionized water according to the weight proportions.
[0044] Furthermore, in this embodiment, the mass ratio of aluminum dihydrogen phosphate resin to the non-sintering repair curing agent used in the repair is 3.5:1.
[0045] Example 3:
[0046] The difference between this embodiment and Embodiment 1 is that in this embodiment, step S1 involves weighing 50 parts of phosphoric acid, 30 parts of phosphate, 10 parts of aluminum hydroxide, 15 parts of magnesium oxide, 2 parts of zirconium oxide, 3 parts of polymer precursor ceramic, 1 part of rare earth zirconate, 2 parts of high entropy ceramic powder, 100 parts of organic solvent, and 100 parts of deionized water according to the weight proportions.
[0047] Furthermore, in this embodiment, the mass ratio of aluminum dihydrogen phosphate resin to the non-sintering repair curing agent used in the repair is 3.5:1.
[0048] Example 4:
[0049] The difference between this embodiment and Embodiment 1 is that in this embodiment, step S1 involves weighing 50 parts of phosphoric acid, 20 parts of phosphate, 10 parts of aluminum hydroxide, 8 parts of magnesium oxide, 2 parts of zirconium oxide, 3 parts of polymer precursor ceramic, 1 part of rare earth zirconate, 2 parts of high entropy ceramic powder, 100 parts of organic solvent, and 100 parts of deionized water according to the weight proportions.
[0050] Furthermore, in this embodiment, the mass ratio of aluminum dihydrogen phosphate resin to the non-sintering repair curing agent used in the repair is 3:1.
[0051] Example 5:
[0052] The difference between this embodiment and Embodiment 1 is that the mass ratio of aluminum dihydrogen phosphate resin to the non-sintering repair curing agent used in this embodiment is 4:1.
[0053] Example 6:
[0054] A repair method for the ceramic thermal protection structure repair agent described in Examples 1-5 includes the following steps:
[0055] Step 1. Use 200-800 grit sandpaper to sand the cracked areas on the coating surface, and then blow the repaired surface clean with clean air to obtain the pre-treated damaged area of the coating.
[0056] Step 2. Mix aluminum dihydrogen phosphate resin and non-sintering repair curing agent at a mass ratio of 3~4:1 to obtain the repair material;
[0057] Step 3. Apply repair material multiple times to the damaged area of the pretreated coating, so that the repaired surface is 1-2 mm higher than the initial surface;
[0058] Step 4. Use an infrared spotlight to heat the surface at 100–120°C for 10–15 hours at a distance of 5–10 cm from the surface to be repaired, in order to remove the solvent and solidify the material.
[0059] Step 5. After the repaired surface has cooled to room temperature, apply 5-10 wt% ammonia solution to the repaired surface 7-8 times, and seal it with plastic wrap for 40-50 minutes.
[0060] Step 6. Remove the plastic wrap, adjust the infrared spotlight to 120–150 ℃, heat it at a distance of 5–10 cm from the surface to be repaired for 6–8 hours to remove residual ammonia, and then let it stand for 24–48 hours to complete the surface repair.
[0061] Using the above-mentioned repair agent and repair method, the repaired ceramic thermal protection structure was obtained. The specific test results are shown in Table 1.
[0062] Table 1
[0063]
[0064] As can be seen from Table 1, the ceramic thermal protection structure repaired in Case 1 has an intact appearance without cracks, and all indicators such as emissivity, surface roughness, step difference and pull-out performance meet the requirements, showing the best overall performance.
[0065] It should be noted that relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0066] Although this application has been described above with reference to specific embodiments, various modifications can be made and components can be replaced with equivalents without departing from the scope of this application. In particular, as long as there is no structural conflict, the features in the specific embodiments disclosed in this application can be combined with each other in any way. The lack of an exhaustive description of these combinations in this specification is merely for the sake of brevity and resource conservation. Therefore, this application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing a ceramic thermal protection structural repair agent, characterized in that, Includes the following steps: S1. Weigh out 40-60 parts of phosphoric acid, 14-30 parts of phosphate, 10-20 parts of aluminum hydroxide, 7-15 parts of magnesium oxide, 1-3 parts of zirconium oxide, 2-5 parts of polymer precursor ceramic, 0.5-2 parts of rare earth zirconate, 1-3 parts of high entropy ceramic powder, 10-100 parts of organic solvent and 10-100 parts of deionized water according to the following weight proportions: S2. Dilute the phosphoric acid obtained in step S1 with deionized water to a mass fraction of 55%, then slowly pour it into aluminum hydroxide at a molar ratio of 1:2, and then place it in a constant temperature water bath at 70~90℃ for 3~4 hours to obtain the first mixture for later use. S3. Place the first mixture obtained in step S1 in a rotary evaporator at 80~110℃, evaporate for 30~40 minutes, and remove it after naturally cooling to room temperature to obtain the second mixture; S4. Add 40 parts of organic solvent to the second mixture obtained in step S2, stir evenly to obtain aluminum dihydrogen phosphate resin, and set aside for use; S5. Place the magnesium oxide, phosphate, polymer precursor ceramic, rare earth zirconate, and high entropy ceramic powder weighed in step S1 into a mixer and stir for 30-50 minutes to obtain the third mixture, which is ready for use. S6. Place the third mixture obtained in step S5 and the zirconium oxide weighed in step S1 into a high-speed shear reactor, then add 60 parts of organic solvent, mix at 3000~4000 rpm for 30~50 min; then dry grind at 150~350 rpm for 3~4 h using a ball mill to obtain a non-sintering repair curing agent. After separating the aluminum dihydrogen phosphate resin obtained in step S4 and the non-sintering repair curing agent, obtain a ceramic thermal protection structure repair agent.
2. The preparation method of the ceramic thermal protection structure repair agent according to claim 1, characterized in that, The polymer precursor in step S1 is polyborosilazane.
3. The preparation method of the ceramic thermal protection structure repair agent according to claim 1, characterized in that, The rare earth zirconate in step S1 is composed of La2Zr2O7.
4. The preparation method of the ceramic thermal protection structure repair agent according to claim 1, characterized in that, The high-entropy ceramic powder in step S1 has the following composition: Yb 0.2 Ho 0.2 Er 0.2 Lu 0.2 , Tb 0.2 )2Si2O7, with a particle size of 400~800 nm.
5. The preparation method of the ceramic thermal protection structure repair agent according to claim 1, characterized in that, The organic solvent in step S1 is ethanol.
6. The preparation method of the ceramic thermal protection structure repair agent according to claim 1, characterized in that, The concentration of phosphoric acid in step S1 is 85 wt%.
7. A ceramic thermal protection structure repair agent according to any one of claims 1 to 6, characterized in that, This includes aluminum dihydrogen phosphate resin and a non-sintering repair and curing agent.
8. A repair method for a ceramic thermal protection structure repair agent as described in claim 7, characterized in that, Includes the following steps: Step 1. Use 200~800 grit sandpaper to sand the cracked area on the coating surface, and then blow the repaired surface clean with clean air to obtain the pre-treated damaged area of the coating. Step 2. Mix aluminum dihydrogen phosphate resin and non-sintering repair curing agent at a mass ratio of 3~4:1 to obtain the repair material; Step 3. Apply repair material multiple times to the damaged area of the pretreated coating, so that the repaired surface is 1-2 mm higher than the initial surface; Step 4. Use an infrared spotlight to heat the surface at 100–120°C for 10–15 hours at a distance of 5–10 cm from the surface to be repaired, in order to remove the solvent and solidify the material. Step 5. After the repaired surface has cooled to room temperature, apply 5-10 wt% ammonia solution to the repaired surface 7-8 times, and seal it with plastic wrap for 40-50 minutes. Step 6. Remove the plastic wrap, adjust the infrared spotlight to 120–150 ℃, heat it at a distance of 5–10 cm from the surface to be repaired for 6–8 hours to remove residual ammonia, and then let it stand for 24–48 hours to complete the surface repair.
Citation Information
Patent Citations
Repairing agent for aircraft ceramic-based heat-proof material and repairing method of repairing agent
CN117285372A